Manajemen Komunikasi “Bidan Delima” Kota Bandung - Saleha Rodiah (MediaTor (Jurnal Komunikasi), 2007)
To become a private midwife with the tittle of bidan delima, one’s should be able not only to communicate both in verbal and non verbal communication but also able to manage a positive impression management. The study is conducted in qualitative method by the perspective of phenomenology and it is aimed to know about bidan delima’s effort in managing their communication act. The result of study has shown that midwives and their clients performed the communication management in form of interpersonal and intrapersonal communication both in a verbal and nonverbal manner. Then, in forms of verbal communication, the informants used mother tongue, informal language, warnings, greetings, and motivation. While in forms of nonverbal communication, the informants performed body gesture, touch, time management, status mark, competition, and identification. Moreover, the bidan delima performed their verbal communication mostly in spoken language, friendly greetings, and as the symbols of their nonverbal communication towards their client, they performed face expression, touch, time schedule, status mark, competition, and identification board. The other result of the study has shown that in terms of the bidan delima’s value of communication competence, the informants have enriched their value by adding ethics, experiences, and positive self-concepts into their communication act. Therefore, based on the result above, the author created a model of bidan delima’s communication management.